Fluorescent Pseudomonas spp. from suppressive and conducive soils share genomic and functional traits relevant to Fusarium graminearum disease suppression - Todorović, Irena; Abrouk, Danis; Kyselková, Martina; Rey, Marjolaine; López-Mondéjar, Rubén; Raičević, Vera; Jovičić-Petrović, Jelena; Moënne-Loccoz, Yvan; Muller, Daniel (BMC genomics, 2025)
BACKGROUND: Soils suppressive to fungal pathogens harbor microbiomes that can inhibit disease development despite the presence of virulent pathogens and susceptible hosts. Fluorescent Pseudomonas are often implicated in such suppressiveness, but their genomic determinants and distribution in suppressive vs. non-suppressive (i.e., conducive) soils remain unclear. RESULTS: We investigated the taxonomic and functional diversity of Pseudomonas populations from wheat rhizospheres in four agricultural soils with contrasting suppressiveness to Fusarium graminearum-induced seedling disease. rpoD-based metabarcoding and culture-dependent isolation revealed distinct Pseudomonas community structures linked to soil suppressiveness. However, major phylogenetic groups were shared across soils. From 406 isolates, 29 representative strains spanning seven subgroups of the P. fluorescens group were selected for whole-genome sequencing. Comparative genomics revealed 14 putative novel Pseudomonas genomospecies (dDDH < 70% with closest described type strains). Genomic screening revealed wide distribution of genes linked to biocontrol and plant-growth promotion, including siderophore biosynthesis, hormone modulation, phosphate solubilization, and production of antimicrobial compounds. Biosynthetic genes for phenazine and pyrrolnitrin were detected exclusively in P. chlororaphis strains isolated from suppressive soils, and rpoD alleles corresponding to these strains were not found in conducive soils within our metabarcoding dataset. Other traits such as hydrogen cyanide, ACC deaminase, and auxin biosynthesis were broadly distributed across isolates from all soils. Functional assays demonstrated variable expression of predicted traits, indicating regulatory or environmental influence. Several strains inhibited F. graminearum mycelial growth via volatile organic compounds, while two strains also reduced conidia germination, including isolates from both suppressive and conducive soils. CONCLUSIONS: This study demonstrates that Pseudomonas genomic traits important for biocontrol are not restricted to suppressive soils, and that functional redundancy and context-dependent expression may shape the contribution of Pseudomonas to disease suppression. Our results highlight the need for integrative analyses combining community profiling, genome-based prediction, and phenotyping to better understand microbiome-mediated plant protection. The identification of novel genomospecies and lineage-specific biosynthetic traits advances our knowledge of Pseudomonas diversity in agricultural soils and supports future development of targeted microbial consortia.
Keywords: půdní mikrobiologie; PGPR; genomika; rhizosféra; Triticum; Soil Microbiology; Diversity; pšenice; fylogeneze; nemoci rostlin; Comparative genomics; Fusarium; Biocontrol agents; Phytopathogens; Genomics; Phylogeny; Pseudomonas; Pseudomonas fluorescens; Plant Diseases; Rhizosphere